Pelatihan Kewirausahaan dalam Meningkatkan Perekonomian Masyarakat Sebagai Upaya Pencegahan Stunting di Kampung Rebegedung Kecamatan Silih Nara Kabupaten Aceh Tengah - Ratnawati, Ratnawati; Saputra, Meli; Khairunnisa, Indah; Juliana, Putri; Mahara, Husnah; Mahara, Emi; Aditiya, Syahrin; Fatimah, Siti; Melana, Lilis; Kapura Sary, Dwi; Wahdini, Wahdini; Ayu, Maulida; Aminah, Aminah; Reza, Muhammad; Finte Nate, Aisya (Universitas Gajah Putih, Indonesia, 2023)
This service was carried out in Rebegedung Village, Silih Nara District, Central Aceh Regency. Most of the livelihoods of the people of Rebegedung Village are farmers, so this service focuses on the economy. The aim of this service is to be able to provide and motivate us as students to learn and practice social awareness by being directly involved in the field. The benefit of this service is to develop a sense of professionalism within oneself with the program that one has so that the program is carried out precisely and accurately so that first analyzing the main program, additional and religious programs with careful planning regarding the methods and stages of implementation as well as evaluation of the main program so that it has positive value in the eyes of the community and train good, transparent and mutually inspiring cooperation and also train the ability to solve problems by adapting, interacting and socializing with the community. The methods used in this service are direct observation and interviews. The problem that occurs in Rebegedung Village is the lack of innovation regarding products produced from the agricultural products of the Rebegedung Village community. So the main program focuses on the economy and the innovative products that have been socialized are Naget Ikan Lele, Boncabe and Oil Chili. The main ingredients are from the agricultural products of the Rebegedung Village Community.